HIV Infection and Liver Disease: A Tertiary Care Centre Study - Sharma, Vandana; Mishra, Sandhya (Indian journal of clinical biochemistry, 2022)
Diseases of hepato-biliary system is a major problem in patients with HIV infection. It has been estimated that approximately one third of the death of patients with HIV infection are in some way related to liver disease. Liver disease in HIV patient is attributed by co-infection with Hepatitis Bor C, drug hepatotoxioity, fatty liver and alcohol abuse. It is also a reflection of the hepatic injury in the form of hepatic steatosis that can be due to antiretroviral therapy. There had been little work done on liver function tests in HIV patients without pre-existing liver disease. So, this study was designed to assess the pattern of liver function tests derangement in HIV patients. To study different patterns of hepatobiliary involvement in HIV positive patients, and to assess its severity, we study included 100 HIV positive patients coming to SMS hospital and Medical College, Jaipur, in medicine and HIV clinic of skin and VD department. Subjects having HIV test positive by ELISA, are included in this study. Other systemic causes of pre-existing liver disease were excluded from the study. Out of 100 cases, 83 were male and 17 were female with mean age 38.12 [+ or -] 32 years. Out of these, 17 patients had coexisting HBV infection and 4 patients had HCV infection.73 cases had abnormal liver function tests in the form of raised AST, ALT, total bilirubin in 54, 68 and 37 patients respectively. Cholesteric pattern of liver injury was found in 41 patients with raised serum Alkaline phosphatase. Evidence of stones in biliary system was found in 13 patients. Thus, almost all types of liver disease were found in HIV patients. The pattern of hepatobiliary involvement varied from asymptomatic elevation of liver function tests to clinically significant liver disease in HIV patients. Prompt diagnosis and treatment required to decrease morbidity.